Unresolved Injustice: An Examination of Indigenous Legal Issues in Australia - Asher, Rachael (Udayana Journal of Law and Culture; Vol 4 No 2 (2020), 2020)
Indigenous legal issues are to some extent a neglected and misunderstood subject in the Australian political and legal sphere. W here there is unresolved injustice, there is suffering. Similarly, where there is misunderstanding, there is ignorance. Therefore, the purpose of this paper is to explore Indigenous legal issues and potential solutions through an examination and analysis of relevant sources. The subjects of discussion in this paper include the limited extent that Aboriginal customary law is recognised under Commonwealth law; the impact of Australian law on Indigenous people; the over-representation of Indigenous people in the criminal justice system; the inadequate state of Indigenous property rights; and comparative law methodology.